A systematic literature review of the clinical signs and symptoms of veno‐occlusive disease/sinusoidal obstruction syndrome after haematopoietic cell transplantation in adults and children. Issue 1 (29th November 2022) - Angus, James; Connolly, Shannon; Letton, William; Martin, Chris; Martin, Alison
Abstract: Veno‐occlusive disease/sinusoidal obstruction syndrome (VOD/SOS) is a rare, serious complication following haematopoietic cell transplantation (HCT). This systematic literature review evaluated differences in clinical manifestations of VOD/SOS post‐HCT in adults and children. Medline and Embase were searched up to 4 March 2021 for reports of VOD/SOS post‐HCT; VOD/SOS diagnostic guidelines were included. Publications were evaluated based on inclusion of five cardinal clinical features of VOD/SOS (ascites, hepatomegaly, hyperbilirubinaemia, right upper quadrant [RUQ] pain and weight gain ≥5%). Overall, 204 publications were included. At diagnosis, hyperbilirubinaemia was more common in adults (93%) versus children (82%), weight gain ≥5% and hepatomegaly were more common in children (86%, 89%) versus adults (73%, 76%) and ascites and RUQ pain were similar between age groups. While 40% of cases had all five cardinal features, age was not a substantial determinant of the likelihood of missing any single specific feature. The proportion of cases, where hyperbilirubinaemia was the first recorded feature, was higher in children versus adults; weight gain and RUQ pain appeared first in a greater proportion of adults versus children. VOD/SOS diagnosis can be challenging; features may not present in a distinct sequence. This necessitates continuous vigilance by those involved in patient monitoring post‐HCT.